High-resolution reconstructions of South America plate motion relative to Africa, Antarctica and North America: 34 Ma to present. Issue 3 (17th February 2019) - DeMets, C; Merkouriev, S
SUMMARY: From an inversion of ≈7000 crossings of 37 magnetic reversals between chrons C1n (0.78 Ma) and C13 (33.7 Ma) and numerous crossings of 43 transform faults and fracture zones in the central and southern Atlantic basin, we estimate finite rotations and stage angular velocities that describe South America plate motion relative to Africa (Nubia), and via plate circuit closures relative to the Antarctic and North America plates. Our newly estimated Nubia–South America rotations, which are spaced at ≈1-Myr intervals, reveal for the first time a transition from steady motion before 24–22 Ma to continuously slowing motion since 20 Ma, including a previously unknown, sudden spreading rate slowdown at 7–6 Ma, when similar declines in seafloor spreading rates also occurred in the northern Atlantic and Arctic basins and along the Southwest Indian Ridge. Geodetic measurements from Nubia and South America, which record the instantaneous plate motion, corroborate the slowdown and indicate it has continued to the present. Our newly determined North America–South America rotations and angular velocities indicate that the pole for this plate pair was stationary from 20 to 12 Ma, but has migrated steadily southward since ≈12 Ma, causing the plate motion direction to change by up to 90° anticlockwise along parts of the diffuse oceanic plate boundary. Since ≈14 Ma, the plate motion rates have averaged 3±0.5 mm yr −1 of N–S to NW–SE-directed divergence near the Mid-Atlantic Ridge and 1–2 mm yr −1 of obliquely convergent motion near the Lesser Antilles Trench, consistent with geodetic estimates. Our new Antarctic–South America rotations and angular velocities predict that American–Antarctic Ridge seafloor spreading rates and plate slip directions have slowed gradually by 60 per cent and rotated 5–7° clockwise since 20 Ma in response to the post-20 Ma slowdown in Nubia–South America seafloor spreading rates. Fracture zone flow lines that are predicted with the new Antarctic–South America rotations agree well with the trends of fracture zone valleys and ridges that flank the American–Antarctic Ridge, offering independent evidence for the accuracy of our new rotations. The Antarctic–South America rotations for chrons C5n.2 (11.1 Ma) and C6no (19.7 Ma) predict that 15–40 km less seafloor has accreted since these times than is indicated by identifications of these two reversals along the American–Antarctic Ridge. Slow westwards movement of the previously postulated Sur microplate with respect to the South America plate may explain the discrepancy—a strong test of this hypothesis awaits better magnetic anomaly data from this remote seafloor spreading centre.